Choosing of turbo compressor rotor surface restoration methods - Dashyvets, Halyna; Suliz, Y.; Дашивець, Галина Іванівна (Запоріжжя : ТДАТУ, 2023)
EN: At present, considerable experience has been accumulated in the restoration of turbocharger rotors. The technological process consists of restoration methods that ensure the required level of operational properties of restored parts. The restored part of the rotor is the shaft. Taking into account the possibility of restoring the shaft in several ways (the method of repair sizes, galvanic build-up – chrome plating, iron plating and the electro sparking method of building up), it is necessary to substantiate and choose a rational technological method of restoration. The method of three criteria (technological, technical, technoeconomic) is usually used to choose a rational technological method of restoring the surfaces of parts. But the multi-criteria choice based on the distance to the goal – the Pareto analysis method allows you to reach the effective frontier, which unites options dominating over others.
Keywords: the turbocharger rotor shaft; productivity; properties of the coatings; resistance of the coatings; lack of thermal impact on the part